Constructing Modern Indonesia Based on Pancasila in Dialogue with the Political Concepts Underlying the Idea of Human Rights - Otto Gusti Ndegong Madung; Winibaldus Stefanus Mere (Jember University Press, 2021)
This article aims to describe the role of Pancasila as an ideological basis and collective identity for the multicultural society of Indonesia. Pancasila has historically been proven to be able to unite Indonesia’s diverse peoples and cultures. Pancasila means five principles that construct the ethical basis for one common home, i.e. Indonesia. The principles are belief in one God, humanity, Indonesia’s national unity, representative democracy, and social justice for all Indonesian citizens. This article argues that in the midst of democratisation and the openness to globalisation, Pancasila needs to be re-interpreted and given a place in contemporary political discourse. It proposes that Pancasila should be read in the light of the contemporary political discourse between communitarianism and liberalism. Such a dialogue is fundamental to coping with the dogmatisation of Pancasila, which can result in the loss of its political relevance as a collective identity. Furthermore, liberalism and communitarianism are the two fundamental philosophical pillars beside socialism upon which the concept of human rights is developed. Therefore, combining Pancasila with the two philosophical concepts is very important to strengthen the role of Pancasila in promoting the idea and practices of human rights politics in Indonesia.